Analisis Penggunaan Surveymeter Ionization Chamber dalam Pengukuran Kebocoran dan Paparan Radiasi di Rumah Sakit - Elyka Elyka; Andi Wahida; Erlinda Ratnasari Putri (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2026)
Radiation safety is an essential aspect of hospital operations that utilize ionizing radiation sources; therefore, continuous monitoring of radiation exposure and leakage is required to protect radiation workers, patients, and the surrounding community. Uncontrolled radiation exposure may pose health risks, highlighting the need for reliable and accurate measurement instruments. This study employs a systematic literature review of 17 scientific articles published between 2021 and 2025 to analyze the effectiveness of ionization chamber–based survey meters in measuring radiation leakage and exposure in hospital environments. The reviewed studies utilized ionization chamber survey meters to evaluate environmental radiation dose rates, occupational exposure of radiation workers, and radiation leakage from medical equipment across various clinical modalities. Several types of ionization chambers were reported, including pressurized ionization chamber survey meters and Farmer ionization chambers. The results indicate that ionization chamber–based survey meters exhibit high measurement accuracy and stability and are capable of consistently detecting radiation exposure and leakage under diverse clinical conditions. The measured radiation exposure and leakage values were generally below the dose limit values established by radiation safety regulations. Therefore, ionization chamber survey meters are effective instruments for supporting environmental dose control, the implementation of the ALARA principle, and the fulfillment of radiation safety standards in hospitals.